This Land is My Land: Teachers' integration of game and novel in English instruction - Ahmadian, Shilan; Brevik, Lisbeth M. (Journal of computer assisted learning, 2024)
Background The most recent Norwegian educational reform, in force from 2020, was the first to include games alongside more traditional language learning resources (e.g., novels, films, music) in the English curriculum for secondary school. This educational emphasis on games provided a unique opportunity to examine how games are actually used in secondary English instruction in combination with other resources. Objectives The aim of this study was to investigate how the digital commercial game This Land is My Land was used alongside a printed novel in naturally occurring English instruction in two lower secondary classes during a two‐week project labelled ‘The Native American Experience’. Methods Participants involved one teacher, nine student teachers and 52 students (aged 13–14). Using a mixed methods design, we integrated quantitative and qualitative analyses of classroom video recordings (N = 20), screen recordings during gameplay (N = 32), student texts (N = 32) and retrospective student interviews (N = 7). We used the validated Protocol for Language Arts Teaching Observation (PLATO; Grossman, 2015) for analyses of video and screen recordings and reflexive thematic analysis (Braun & Clarke, 2022) of student texts and interviews. Results and Conclusions The combination of digital game and printed novel during English instruction provided a dual perspective on the Native American experience. While the novel provided a window for observing the topic historically, the game provided a playground to experience the topic interactively. Although the combination of game and novel offered students different perspectives on the Native American experience, we identified missed opportunities for those who gamed before reading, whereas students who read before gameplay used their knowledge from the novel when they engaged with the game content. In the broader context of educational technology and language instruction, this study identified how to combine digital and traditional literacies that acknowledge students' prior knowledge with diverse literacies. Lay Description What is already known about this topic Digital games are the most popular literacy used by young people worldwide. Teachers implement digital games as part of their instruction, but often games that are designed for educational purposes. When teachers use digital games that are not designed for educational purposes, that is, commercial games, it often involves researcher intervention. What this paper adds Observational research on instruction that involved a commercial game in two English classes in Norway, completely without researcher intervention. Commercial gameplay was an integrated part of the English instruction and used in combination with reading a printed novel. The combination of gameplay and reading provided students with different perspectives and experiences on the same topic Implications of study for practitioners Teachers should use commercial games as an integrated part of their English instruction for subject‐specific purposes. Student engagement in learning might be enhanced when commercial games are used in combination with literature. It might be beneficial to have a pre‐reading activity before gameplay, to provide background knowledge.